Method for determining addition amount of electrolyte low-temperature additive

By adding thickener and low-temperature additives to the electrolyte and conducting rheology tests, the target addition amount of the electrolyte is determined, which solves the problem of high cost of assembling batteries in traditional methods, and achieves low-cost and fast adaptable low-temperature additives The concentration is determined, which improves the performance of the battery in low temperature environments.

CN119178699APending Publication Date: 2024-12-24REPT BATTERO ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411548299.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Traditional methods determine the amount of low-temperature additives for battery electrolyte in a low-temperature environment require assembling the battery for testing, which is costly and inefficient, and it is difficult to quickly adapt to complex operating conditions.

Method used

By providing the electrolyte standard sample, adding thickener and stirring to form the first solution, divided into multiple portions and adding low-temperature additives, refrigeration and rheology tests, including continuous shear rate tests, to determine the target addition amount, avoiding Verify directly assemble the battery.

Benefits of technology

It saves the verification cost of assembling batteries, can quickly find the appropriate low-temperature additive concentration, adapt to different working conditions, and reduces the performance loss of batteries in low-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119178699A_ABST
    Figure CN119178699A_ABST
Patent Text Reader

Abstract

The invention provides a method for determining the addition amount of an electrolyte low-temperature additive, and relates to the field of energy storage. The method comprises the following steps: providing an electrolyte standard sample; adding a thickening agent into the electrolyte standard sample, and stirring to obtain a first solution; dividing the first solution into N parts, and respectively adding the N parts of low-temperature additives into the N parts of the first solution to obtain N parts of second solutions; freezing the N parts of the second solution and then carrying out rheological property test, the rheological property test comprises continuous first shear rate test, second shear rate test and third shear rate test, and first viscosity data, second viscosity data and third viscosity data are respectively obtained; and according to the first viscosity data and the third viscosity data obtained by each second solution, determining a target addition amount of the low-temperature additive based on a preset condition. According to the method provided by the invention, battery assembly is not needed, the optimal addition amount of the low-temperature additive is determined based on the viscosity value, and the verification cost of battery assembly is saved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of energy storage technology, and in particular to a method for determining the amount of a low-temperature additive added to an electrolyte. Background Art

[0002] The electrolyte is the medium for ion transfer. Ions shuttle back and forth between the positive electrode and the negative electrode. The shuttle speed is affected by factors such as temperature, electrolyte conductivity, and electrolyte viscosity. With the development of battery technology, batteries are used in different working conditions, and low temperature conditions are an important factor restricting battery performance.

[0003] In traditional technology, in order to prevent the performance of the battery from deteriorating in a low temperature environment, a low-temperature electrolyte additive is added to the battery. In order to determine the optimal amount of addition, the conventional operation is to add the low-temperature electrolyte additive to the electrolyte in different proportions, and then use a soft-pack or square battery for testing.

[0004] However, the method used by traditional technology requires the battery to be assembled before the test results can be obtained, which requires the consumption of the electrolyte and battery shell injected into the entire battery, and the verification cost is relatively high. Summary of the invention

[0005] Based on this, it is necessary to provide a method for determining the proportion of low-temperature additives in the electrolyte, which can determine the amount of low-temperature additives added to the electrolyte at a low cost.

[0006] A method for determining the amount of electrolyte low-temperature additives, comprising the following steps:

[0007] Provide electrolyte standard samples;

[0008] adding a thickener to the electrolyte standard sample and stirring to obtain a first solution;

[0009] Dividing the first solution into N parts, and adding N parts of the low-temperature additive to N parts of the first solution respectively, to obtain N parts of the second solution; wherein N ≥ 2, and the mass content of the low-temperature additive in the N parts of the second solution is different;

[0010] The N portions of the second solution are subjected to freezing treatment and rheological test in sequence, wherein the rheological test includes a first shear rate test, a second shear rate test and a third shear rate test in succession, and first viscosity data, second viscosity data and third viscosity data are obtained respectively; wherein the shear rate value in the second shear rate test is greater than the shear rate values ​​in the first shear rate test and the third shear rate test;

[0011] According to the first viscosity data and the third viscosity data obtained for each of the second solutions, a target addition amount of the low-temperature additive in the electrolyte standard sample is determined based on preset conditions.

[0012] In some embodiments, the mass content of the thickener in the first solution is 0.5% to 10%.

[0013] In some embodiments, the thickener includes one or more of polytetrafluoroethylene, polyurethane resin, polyvinylidene fluoride, styrene-butadiene rubber latex, carboxymethyl cellulose, polyacrylic acid, polyacrylonitrile and polyacrylate.

[0014] In some embodiments, the viscosity of the first solution is 500 PaS~2000 PaS.

[0015] In some embodiments, the freezing treatment is performed at a temperature of -60°C to 0°C and for a time of 1 hour to 48 hours.

[0016] In some embodiments, the mass content of the low-temperature additive in the second solution is 0.1% to 10%.

[0017] In some embodiments, the low-temperature additive includes one or more of N,N-dimethyltrifluoroacetamide, sulfones, organic sulfites, fluoroethylene carbonate and vinylene carbonate.

[0018] In some embodiments, the mass content of the low-temperature additive in the N parts of the second solution is arranged in a gradient.

[0019] In some embodiments, the preset conditions include: in the third shear rate test, the addition amount of the low-temperature additive corresponding to the second solution whose absolute value of the difference between the third viscosity data and the first viscosity data within a preset time is within a preset range is used as the target addition amount.

[0020] In some implementation modes, the preset conditions include:

[0021] There are multiple second solutions whose absolute value of the difference between the third viscosity data and the first viscosity data is within a preset range within a preset time, and the multiple second solutions are used as candidate solutions;

[0022] The one with the least amount of low-temperature additive added among the multiple candidate solutions is used as the target addition amount.

[0023] In the above-mentioned method for determining the amount of low-temperature additives added to the electrolyte, the electrolyte standard sample is used as the base solution, and the thickener is added to first reduce the fluidity of the electrolyte, and the viscosity is adjusted after stirring evenly so that the fluidity of the electrolyte can be quantified to obtain a first solution. After that, the first solution is divided into N parts, and N parts of the addition amount are set to be added to N parts of the first solution respectively to obtain N parts of the second solution. After freezing the N parts of the second solution, a rheological test is performed, including a continuous first shear rate test, a second shear rate test, and a third shear rate test, to obtain the first viscosity data, the second viscosity data, and the third viscosity data, respectively. For the case of good fluidity, the third viscosity data obtained in the third shear rate test can be equal to or approximately equal to the first viscosity data, so the target addition amount of the low-temperature additive can be determined according to the rheological test results of each second solution according to the preset conditions. Compared with the method of setting an electrolyte with different addition amounts of low-temperature additives in the conventional technology, and then assembling the battery and testing to determine the target addition amount, the method provided in the present application does not require the assembly of the battery, and determines the optimal addition amount of the low-temperature additive based on the rheological test results, saving the verification cost of assembling the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 A schematic flow chart of a method for determining the amount of a low-temperature additive to an electrolyte according to an embodiment of the present invention;

[0025] Figure 2 This is a rheological curve diagram of the first solution after adding a thickener and stirring in one embodiment;

[0026] Figure 3 is a rheological curve diagram of each second solution after freezing treatment in one embodiment;

[0027] Figure 4 The performance test diagram of the battery prepared by each second solution in one embodiment. DETAILED DESCRIPTION

[0028] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0030] The mechanism of action of low-temperature additives in batteries is to lower the freezing point of the electrolyte, so that it can maintain good fluidity and conductivity in low-temperature environments. There are several usage scenarios for batteries in low-temperature environments. One is that the equipment is only in a low-temperature environment during working hours; the second is that the equipment stays in a low-temperature environment for a long time and the working time is short; the third is that the equipment does not work in a low-temperature environment for a long time.

[0031] A battery that has not been used for a long time in a low-temperature environment is difficult to start. The method provided by the present invention can be used to quickly find a suitable low-temperature additive concentration for complex battery operating conditions.

[0032] See also Figure 1 , a method for determining the amount of low-temperature additive to be added to an electrolyte, comprising the following steps S11 to S14.

[0033] S11, provide electrolyte standard sample.

[0034] For example, the electrolyte standard sample may be an electrolyte product that needs to be added with a low-temperature additive. For example, after configuring the material selection and component content of each component in the electrolyte according to the use conditions, the electrolyte standard sample is configured.

[0035] That is, illustratively, the electrolyte standard sample is consistent with the electrolyte system of the finished electrolyte of the target finished battery except for the low-temperature additive. In this way, the measured amount of low-temperature additive added is also the amount of the low-temperature additive added in the electrolyte standard sample. Therefore, by directly applying the added amount of low-temperature additive to the electrolyte standard sample, a finished electrolyte that can be directly adapted to the target finished battery can be obtained.

[0036] S12, adding a thickener to the electrolyte standard sample, stirring to obtain a first solution.

[0037] For example, the stirring speed may be 400 rpm to 1000 rpm, and the stirring time may be 0.5 h to 3 h. For example, the stirring speed may be, but not limited to, 400 rpm, 500 rpm, 600 rpm, 700 rpm, 800 rpm, 900 rpm or 1000 rpm, and the stirring time may be, but not limited to, 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h or 3 h.

[0038] S13, dividing the first solution into N parts, and adding N parts of the low-temperature additive to the N parts of the first solution respectively to obtain N parts of the second solution; wherein N ≥ 2, and the mass content of the low-temperature additive in the N parts of the second solution is different.

[0039] Exemplarily, the same or different amounts of low-temperature additives may be added to the N first solutions. Optionally, the amounts of low-temperature additives added to the N first solutions are different, or at least two of the amounts of low-temperature additives added to the N first solutions are the same.

[0040] Exemplarily, adding N portions of low-temperature additives to N portions of the first solution in different amounts respectively means that only one portion of low-temperature additive is added to one portion of the first solution, and different portions of the first solution have different amounts of the low-temperature additive added.

[0041] Exemplarily, the added amount refers to the mass percentage of the low-temperature additive in the second solution after the low-temperature additive is added to the first solution to obtain the second solution.

[0042] S14, freezing treatment and rheological test are performed on N portions of the second solution in sequence, wherein the rheological test includes a continuous first shear rate test, a second shear rate test and a third shear rate test, and first viscosity data, second viscosity data and third viscosity data are obtained respectively. The shear rate value in the second shear rate test is greater than the shear rate values ​​in the first shear rate test and the third shear rate test.

[0043] Exemplarily, the freezing treatment refers to placing the second solution in a cooling environment. Optionally, the cooling environment may be a low temperature use environment of the target finished battery.

[0044] Exemplarily, the rheological test may be a 3ITT test (Three-Interval-Time-Test), which includes three test stages, namely, a first shear rate test, a second shear rate test, and a third shear rate test. The first shear rate test is a first low shear rate stage, the second shear rate test is a high shear rate stage, and the third shear rate test is a second low shear rate stage. Optionally,

[0045] The shear rate in the first shear rate test can be 0.01~0.1s -1 The shear rate in the second shear rate test can be 10~100s -1 The shear rate in the third shear rate test can be 0.01~0.1s -1 For example, the shear rates of the first low shear rate stage and the second low shear rate stage may be equal or approximately equal.

[0046] In the 3ITT test, the static structure is first evaluated by oscillation in the first time period, then the structure is destroyed by high-speed shear in the second time period, and then the recovery of the structure is evaluated again by oscillation in the third time period.

[0047] S15, determining a target addition amount of the low-temperature additive in the electrolyte standard sample based on preset conditions according to the first viscosity data and the third viscosity data obtained for each second solution.

[0048] For example, in the case of good fluidity, the third viscosity data can be completely restored to the first viscosity data in a short time, and in the case of poor fluidity, the third viscosity data may not be restored to the first viscosity data, or may not be restored within the test time period. Therefore, based on the 3ITT test, the fluidity test conditions of each second solution can be determined according to preset conditions, and the amount of low-temperature additive to be added can be determined.

[0049] Exemplarily, the target addition amount may be an optimal addition amount to solve the fluidity problem of the electrolyte at low temperatures.

[0050] In the above-mentioned method for determining the amount of low-temperature additives added to the electrolyte, the electrolyte standard sample is used as the base solution, and the thickener is added to first reduce the fluidity of the electrolyte, and the viscosity is adjusted after stirring evenly so that the fluidity of the electrolyte can be quantified to obtain a first solution. After that, the first solution is divided into N parts, and N parts of the addition amount are set to be added to N parts of the first solution respectively to obtain N parts of the second solution. After freezing the N parts of the second solution, a rheological test is performed, including a continuous first shear rate test, a second shear rate test, and a third shear rate test, to obtain the first viscosity data, the second viscosity data, and the third viscosity data, respectively. For the case of good fluidity, the third viscosity data obtained in the third shear rate test can be equal to or approximately equal to the first viscosity data, so the target addition amount of the low-temperature additive can be determined according to the rheological test results of each second solution according to the preset conditions. Compared with the method of setting an electrolyte with different addition amounts of low-temperature additives in the conventional technology, and then assembling the battery and testing to determine the target addition amount, the method provided in the present application does not require the assembly of the battery, and determines the optimal addition amount of the low-temperature additive based on the rheological test results, saving the verification cost of assembling the battery.

[0051] In some embodiments, the preset conditions include: in the third shear rate test, the addition amount of the low-temperature additive corresponding to the second solution whose difference between the third viscosity data and the first viscosity data within a preset time is within a preset range is used as the target addition amount.

[0052] Exemplarily, the preset time refers to a period of time at the beginning of the third shear rate test. If the third viscosity data is equal to the first viscosity data within the preset time, or the absolute value of the viscosity difference with the first viscosity data is within the preset range, it indicates that after the high shear force test in the second test phase, the tested solution can still quickly recover to the initial state, indicating good fluidity.

[0053] Optionally, the preset range can be selected according to actual needs, for example, it can be set between 0PaS and 50PaS.

[0054] Optionally, the preset time may also be selected according to actual needs, for example, it may be set within a range of 0.5S-50s.

[0055] If the preset range is set to 30 PaS and the preset time is set to 20 s, then when the third shear rate test starts, if the viscosity value measured at 20 s is within 20 PaS of the viscosity value of the first shear rate test, then the second solution is considered to have good fluidity.

[0056] In other embodiments, the preset conditions include: there are multiple second solutions whose absolute value of the difference between the third viscosity data and the first viscosity data is within a preset range within a preset time, and the multiple second solutions are used as candidate solutions; the one with the least amount of low-temperature additive added among the multiple candidate solutions is used as the target addition amount. It can be explained that in some cases, two or more of the N second solutions can be restored to the absolute value of the difference with the first viscosity data within the preset range, which indicates that the multiple second solutions can meet the fluidity requirements. At this time, the one with the least amount of low-temperature additive added is used as the target addition amount, which can reduce the amount of low-temperature additive added while meeting the fluidity requirements, thereby reducing costs.

[0057] It is understandable that the present application can be applied to batteries with liquid electrolytes such as lithium ion electrolytes, sodium ion electrolytes, lithium metal batteries, and lithium sulfur electrolytes. The present application embodiments are only exemplified by lithium ion electrolytes.

[0058] In some embodiments, the mass content of the thickener in the first solution is 0.5% to 10%. Exemplarily, the mass content of the thickener in the first solution may be, but is not limited to, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%. Within the above range, the fluidity of the electrolyte can be appropriately reduced, which is convenient for quantifying the viscosity change after adding the low-temperature additive, and avoids excessive viscosity resulting in an insignificant viscosity change after adding the low-temperature additive. Further, the mass content of the thickener in the first solution may be 1% to 5%.

[0059] In some embodiments, the thickener includes one or more of polytetrafluoroethylene, polyurethane resin, polyvinylidene fluoride, styrene-butadiene rubber latex, carboxymethyl cellulose, polyacrylic acid, polyacrylonitrile, and polyacrylate.

[0060] In some embodiments, the viscosity of the first solution is 500PaS to 2000PaS. For example, the viscosity of the first solution may be, but is not limited to, 500PaS, 600PaS, 700PaS, 800PaS, 900PaS, 1000PaS, 1100PaS, 1200PaS, 1300PaS, 1400PaS, 1500PaS, 1600PaS, 1700PaS, 1800PaS, 1900PaS or 2000PaS. Within the above range, the viscosity of the first solution is appropriate to avoid the viscosity change after adding the low-temperature additive is not obvious, it is difficult to screen out the appropriate amount of the low-temperature additive.

[0061] In some embodiments, the temperature of the freezing treatment is -60°C to 0°C, and the time is 1h to 48h. Exemplarily, the temperature of the freezing treatment may be, but is not limited to, -60°C, -50°C, -40°C, -30°C, -20°C, -10°C or 0°C. Exemplarily, the time of the freezing treatment may be, but is not limited to, 1h, 2h, 4h, 6h, 10h, 15h, 20h, 25h, 30h, 35h, 40h, 45h or 48h. Within the above range, the low-temperature use scenario of the electrolyte can be simulated, so that the viscosity of the second solution after freezing treatment is closer to the actual use scenario, and the accuracy of the amount of low-temperature additive added is improved.

[0062] In some embodiments, the mass content of the low temperature additive in the first solution is 0.1% to 10%. Exemplarily, the mass content of the low temperature additive in the first solution can be, but is not limited to, 0.1%, 0.2%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.8%, 5%, 5.2%, 5.5%, 5.8%, 6%, 6.2%, 6.5%, 6.8%, 7%, 7.2%, 7.5%, 7.8%, 8%, 8.2%, 8.5%, 8.8%, 9%, 9.2%, 9.5%, 9.8% or 10%. In this way, it can be added to the first solution according to different addition amounts.

[0063] In some embodiments, the concentrations of the low-temperature additives in the N portions of the second solution are arranged in a gradient, that is, the concentrations of the low-temperature additives are in an arithmetic progression.

[0064] Exemplarily, the first solution is divided into 6 parts, and 6 parts of low-temperature additives are added to 6 parts of the first solution in different addition amounts to obtain 6 parts of the second solution. The mass content of the low-temperature additive in the 6 parts of the second solution is 0.5%, 1%, 1.5%, 2%, 2.5%, and 3%, respectively. In this way, by determining the viscosity values ​​of the 6 parts of the second solution, the target addition amount in the above 6 addition amounts can be determined. It is understandable that the comparable addition amount can be broadened by increasing the number of addition amounts.

[0065] In some embodiments, the low temperature additive includes one or more of N,N-dimethyltrifluoroacetamide, sulfones, organic sulfites, fluoroethylene carbonate, and vinylene carbonate.

[0066] In some embodiments, the electrolyte standard sample includes an electrolyte solute and an electrolyte solvent; the electrolyte solute includes one or more of LiPF6, LiClO4, LiBF4, LiBOB, LiAsF6, NaPF6, NaClO4, NaTFSI, NaOTF and NaBF4. And / or, the electrolyte solvent includes one or more of cyclic carbonate, chain carbonate, carboxylic acid ester, 1,2-dimethoxypropane, dimethoxymethane, chain ether, tetrahydrofuran and cyclic ether.

[0067] The following is a specific example. The rheological properties test of this example uses a rheological tester to perform a 3ITT test, including a static phase, a reconstruction phase, and a storage stabilization phase, which are performed in sequence, corresponding to the first shear rate test, the second shear rate test, and the third shear rate test, respectively. The static phase is to test the sample at 0.1s -1 The first shearing was performed at a constant shear rate of 50 s to a steady state. The reconstruction phase was to heat the sample obtained in the static phase at a constant shear rate of 50 s. -1 The second shearing was performed at a constant shear rate of 0.1s to a steady state. The storage stabilization stage was to store the sample obtained in the reconstruction stage at a constant shear rate of 0.1s -1 The third shearing was performed at a constant shear rate until steady state.

[0068] Embodiment 1:

[0069] (1) Provide an electrolyte standard sample. The electrolyte standard sample includes an electrolyte solvent and an electrolyte solute, wherein the electrolyte solvent includes a first solvent, ethylene carbonate, and a second solvent, dimethyl carbonate, and the volume ratio of ethylene carbonate to dimethyl carbonate is 1:1. The electrolyte solute is LiPF6, and the concentration is 1 mol·L -1 .

[0070] (2) Add the thickener polytetrafluoroethylene to the standard electrolyte sample to obtain a first solution, wherein the mass fraction of polytetrafluoroethylene in the first solution is 2%. Stirring at a stirring speed of 500 rpm for 1.5 hours, the viscosity of the first solution is measured to be 1500 PaS. The first solution is subjected to a 3ITT test using a rheological tester, and the results are as follows: Figure 2 shown. Figure 2 The first viscosity data of the first solution in the first shear steady state is 1500 PaS, the second viscosity data in the second shear steady state is 600 PaS, and the viscosity data in the second shear steady state is 1500 PaS.

[0071] Figure 2 is the rheological curve after adding thickener and stirring. Figure 2 It can be seen that the rheological curve of the first solution shows that the thickener is mixed and dispersed in the electrolyte, the rheological curve in the static stage remains stable, and after a high shear rate, the rheology in the reconstruction stage decreases. After the storage stabilization stage, the viscosity immediately returns to the viscosity of the static stage after the shear rate is restored to the static stage, indicating excellent viscoelasticity. This standard sample can be used to characterize the impact of testing low-temperature additives.

[0072] (3) The first solution was divided into 6 parts, and 6 parts of the low-temperature additive N,N-dimethyltrifluoroacetamide were added to the 6 parts of the first solution in different amounts to obtain 6 parts of second solutions, namely the first second solution, the second second solution, the third second solution, the fourth second solution, the fifth second solution and the sixth second solution, wherein the mass percentages of the 6 parts of the low-temperature additive in each of the second solutions were 0.5%, 1%, 1.5%, 2%, 2.5% and 3%, respectively.

[0073] (4) Place 6 portions of the second solution and 1 portion of the electrolyte standard sample in a constant temperature box, set the temperature to -20°C, and let it stand for 6 hours. Then, use a rheometer to perform a 3ITT test on the 6 portions of the second solution and 1 portion of the electrolyte standard sample using the same test conditions as step (3). The results are as follows: Figure 3 shown.

[0074] Figure 3 In the 3ITT test, the viscosity of the electrolyte standard samples is approximately equal to 0.

[0075] like Figure 3 As shown, Figure 3The figure is a rheological curve diagram of 6 parts of the second solution and 1 part of the electrolyte standard sample after cooling treatment. The first second solution to the sixth second solution are defined as additive 0.5%, additive 1%, additive 1.5%, additive 2%, additive 2.5% and additive 3%, respectively, and the electrolyte standard sample is defined as the standard sample. It can be seen from the figure that the viscosity values ​​of the electrolyte standard sample without thickener are close to 0 in the three stages. The mass percentage of the low-temperature additive in the first second solution is 0.5%. There are data fluctuations at the first low shear rate, and it is difficult to reach a steady state. It is also difficult to reach a steady state at the second low shear rate, and the third viscosity data is significantly smaller than the first viscosity data, indicating that its fluidity is poor. The mass percentage of the low-temperature additive in the second second solution is 1%, which can reach a steady state at the first low shear rate. The third viscosity data continues to rise at the second low shear rate, but it does not rise to the first viscosity data within the test time period, indicating that its fluidity is limited. The mass percentage of low-temperature additive in the third second solution is 1.5%, which can reach a steady state at the first low shear rate. The third viscosity data recovers slowly at the second low shear rate, but can be flush with the first viscosity data for a long time, indicating that its fluidity has improved. The mass percentage of low-temperature additive in the fourth second solution is 2%, which can reach a steady state at the first low shear rate. The third viscosity data recovers moderately at the second low shear rate and can be flush with the first viscosity data within a certain period of time, indicating that its fluidity is moderate. The mass percentage of low-temperature additive in the fifth second solution is 2.5%, and the mass percentage of low-temperature additive in the sixth second solution is 3%. Both can reach a steady state at the first low shear rate, and the third viscosity data recovers rapidly at the second low shear rate and can quickly be flush with the first viscosity data, indicating that its fluidity is good.

[0076] For example, with the preset time of 5 seconds, the 2.5% and 3% additives in the 6 portions of the second solution provided in this embodiment meet the requirements, and one of them can be selected as the target addition amount. Further, it can be used as an alternative solution, because the addition amount of the low-temperature additive is less when the addition amount is 2.5%, in order to reduce costs, the addition amount is 2.5% as the target addition amount.

[0077] (5) Three portions of the second solution with 2%, 2.5% and 3% of the low-temperature additive were used as electrolytes to prepare 190Ah batteries. Among them, the positive electrode sheet: the positive electrode active material lithium iron phosphate, the binder PVDF, and the conductive agent SP were added to the solvent N-methylpyrrolidone in a mass ratio of 95:2:3 to make a slurry, and then coated on the positive electrode collector to form a positive electrode active material layer, and rolled to obtain a positive electrode sheet. The negative electrode sheet is: artificial graphite (AG), Super-P, styrene-butadiene latex (SBR) carboxymethyl cellulose (CMC) and mixed and stirred in a mass ratio of 96:0.7:2:1.3, and then evenly coated on the surface of the copper foil, dried at 120°C in vacuum for 12 hours, and sliced ​​to obtain a negative electrode sheet.

[0078] like Figure 4 As shown, the electrochemical performance corresponding to the electrolyte concentration screened by the method provided by the present invention in Example 1, the test conditions are: the three batteries obtained are tested as follows: 1C constant current and constant voltage to 3.65V, cut-off current 0.05C, 1C discharge to 2.5V.

[0079] 2% low-temperature additive can only release 80Ah of capacity, because the low fluidity of the electrolyte leads to relatively large polarization, and the battery quickly reaches the cut-off voltage. The fluidity of 2.5% low-temperature additive has basically recovered, and the battery can release more capacity, reaching 166Ah. The fluidity of 3% low-temperature additive is better, and the capacity reaches 170Ah. It can be seen that the increase of 2.5% to 3% of low-temperature additives cannot have a very obvious improvement on the performance of the battery. Considering the cost of the battery, 2.5% content is used as the target addition amount, which is also the optimal addition amount.

[0080] This also proves that the testing method of the low-temperature additive of the present application is relatively accurate.

[0081] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0082] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for determining the amount of low-temperature additives added to an electrolyte, characterized in that: The following steps are involved: Provide electrolyte standard samples; adding a thickener to the electrolyte standard sample and stirring to obtain a first solution; Dividing the first solution into N parts, and adding N parts of the low-temperature additive to N parts of the first solution respectively, to obtain N parts of the second solution; wherein N ≥ 2, and the mass content of the low-temperature additive in the N parts of the second solution is different; The N portions of the second solution are subjected to freezing treatment and rheological test in sequence, wherein the rheological test includes a first shear rate test, a second shear rate test and a third shear rate test in succession, and first viscosity data, second viscosity data and third viscosity data are obtained respectively; wherein the shear rate value in the second shear rate test is greater than the shear rate values ​​in the first shear rate test and the third shear rate test; According to the first viscosity data and the third viscosity data obtained for each of the second solutions, a target addition amount of the low-temperature additive in the electrolyte standard sample is determined based on preset conditions.

2. The method according to claim 1, characterized in that The mass content of the thickener in the first solution is 0.5% to 10%.

3. The method according to claim 1, characterized in that The thickener includes one or more of polytetrafluoroethylene, polyurethane resin, polyvinylidene fluoride, styrene-butadiene rubber latex, carboxymethyl cellulose, polyacrylic acid, polyacrylonitrile and polyacrylate.

4. The method according to claim 1, characterized in that: The viscosity of the first solution is 500 PaS~2000 PaS.

5. The method according to claim 1, characterized in that The freezing treatment is carried out at a temperature of -60°C to 0°C and for a time of 1h to 48h.

6. The method according to claim 1, characterized in that The mass content of the low-temperature additive in the second solution is 0.1% to 10%.

7. The method according to claim 1, characterized in that The low-temperature additive includes one or more of N,N-dimethyltrifluoroacetamide, sulfones, organic sulfites, fluoroethylene carbonate and vinylene carbonate.

8. The method according to claim 1, characterized in that The mass contents of the low-temperature additive in the N parts of the second solution are arranged in a gradient.

9. The method according to claim 1, characterized in that: The preset condition includes: in the third shear rate test, the addition amount of the low-temperature additive corresponding to the second solution whose absolute value of the difference between the third viscosity data and the first viscosity data within a preset time is within a preset range is used as the target addition amount.

10. The method according to claim 9, characterized in that The preset conditions include: There are multiple second solutions whose absolute value of the difference between the third viscosity data and the first viscosity data is within a preset range within a preset time, and the multiple second solutions are used as candidate solutions; The one with the least amount of low-temperature additive added among the multiple candidate solutions is used as the target addition amount.